2013
DOI: 10.1002/jmri.24114
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging (DTI) of the normal human uterus in vivo at 3 tesla: Comparison of DTI parameters in the different uterine layers

Abstract: Purpose To investigate the differences in the fiber architecture and related diffusion tensor imaging (DTI) parameters among different uterine layers of the normal human uterus in vivo at 3 Tesla (T). Materials and Methods DTI of the uterus was performed for nine healthy women of reproductive age on a 3T scanner. A volume of interest (VOI) was drawn for the outer myometrium (OM), junctional zone (JZ), and endometrium (EM). Apparent diffusion coefficient (ADC), fractional anisotropy (FA), and maximum fiber leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
4
23
0
Order By: Relevance
“…FA values of the three zonal structures of the uterus showed significant difference at each phase during menstrual cycle. The relative order of FA values of these three layers in LP was the same as Fujimoto's studies, 14 reflecting the differences in the density of well-aligned fibre bundles. FA values of each layer in our study were smaller than those in previous studies, which might be explained by the different racial subjects as well as different MR scanners, image quality and ROI measurements in DTI.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…FA values of the three zonal structures of the uterus showed significant difference at each phase during menstrual cycle. The relative order of FA values of these three layers in LP was the same as Fujimoto's studies, 14 reflecting the differences in the density of well-aligned fibre bundles. FA values of each layer in our study were smaller than those in previous studies, which might be explained by the different racial subjects as well as different MR scanners, image quality and ROI measurements in DTI.…”
Section: Discussionsupporting
confidence: 74%
“…Current published studies include ex vivo and in vivo studies. [11][12][13][14][15][16] In 2006, threedimensional fibre architecture of the normal human uterus based on DTI has been ex vivo evaluated in five samples by Weiss et al 11 Toba et al 12 ex vivo study showed that DTI might be a useful tool for the diagnosis of myometrial invasion of uterine endometrial cancer. However, fractional anisotropy (FA) value of a normal uterus has not been thoroughly investigated yet.…”
Section: Yonglan He and Ning Ding Have Contributed Equally To This Armentioning
confidence: 99%
See 1 more Smart Citation
“…1. These values reflect the spatial variation of the shear wave speed and the standard error of the shear wave speed measurement [15] and could be associated with the anisotropy of the uterus [19,18]. While in this study, the probe was positioned in a single position, SSI can be used to assess tissue anisotropy by tilting the probe with different angles around a symmetry axis during contraction as described by Lee et al [23].…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion tensor imaging is the best method to evaluate the anisotropic properties of solid organs, and it, unlike DWI, permits the analysis of diffusion along multiple directions. Recently, the improvement of this technique made it a useful and complementary sequence to conventional imaging techniques for demonstrating the fiber structures of the uterus (4,8,(10)(11)(12)(13).…”
mentioning
confidence: 99%